Alterations of subset and cytokine profile of peripheral T helper cells in PBMCs from Multiple Sclerosis patients or from individuals with MS risk SNPs near genes CYP27B1 and CYP24A1. (May 2022) - Lu, Ming; Shi, Hui; Taylor, Bruce V.; Körner, Heinrich
Abstract: T helper cells play an important role in the aetiology of Multiple Sclerosis (MS). Vitamin D has an anti-inflammatory effect on T helper cells and can affect onset and pathogenesis of MS. Two genes of the metabolic Vitamin D pathway expressed by activated T helper (Th) cells have been identified as MS risk genes by genome-wide association studies, CYP27B1 (25(OH)D3 1-alpha-hydroxylase) and CYP24A1 (1, 25(OH)2 D3 24-alpha-hydroxylase). Therefore, we hypothesize that the MS risk alleles around gene CYP27B1 and CYP24A1 are associated with the altered inflammatory profile of peripheral Th cells in PBMCs both ex vivo and in vitro potentially influencing the pathogenesis of MS. PBMCs from MS patients (41 RRMS patients in their remitting stage and 4 SPMS patients) and 12 healthy controls were collected, subpopulation of Th cells in PBMCs and cytokine profile were tested by Flow cytometry and Cytometric Bead Array (CBA), respectively. MS risk SNPs were genotyped by allele-specific PCR analysis. Data were analysed using nonparametric tests and linear regression for adjusting multiple factors. The proportion of Th17.1, Th17 and Th1 cells were all associated with MS while the proportions of Th2 (significant) and Th17 (near significant) cells were correlated with the expanded disability scale score of MS patients. Additionally, we found a MS-specific dysregulation in the IL-6 and TNF production of Th cells in Concanavalin A-stimulated PBMCs. Furthermore, the risk allele rs2248359-C (near gene CYP24A1 ) showed a consistent inhibitory effect on the proportions of Th1 and Th17.1 cells, and the presence of the homozygous risk allele rs703842-AA (near gene CYP27B1 ) reduced the production of IL-2. In conclusion, both MS disease and its risk alleles near Vitamin D metabolism genes influence the inflammatory profile of T helper cells in PBMCs.